2010
DOI: 10.1111/j.1432-2277.2009.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of hepatic artery thrombosis following liver transplantation

Abstract: Summary Hepatic artery thrombosis (HAT) is the most frequent vascular complication following orthotopic liver transplantation. Urgent retransplantation has been considered as the mainstay therapy. Surgical revascularization is an effective alternative in asymptomatic patients. Endovascular therapies including intra‐arterial thrombolysis, percutaneous transluminal angioplasty (PTA), and stent placement have shown encouraging results in recent years; however, their use remains controversial because of potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
162
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(194 citation statements)
references
References 66 publications
2
162
2
3
Order By: Relevance
“…Many studies show contradictory results [1,9,17,28,41] but, a metaanalysis on HAT found no significant difference with an incidence of 3.1% and 4.6% in LDLT and DDLT, respectively [28] . Furthermore, it was reported that arterial anastomosis with operation microscope or loupe mangnification did not show any difference in incidence HAT [9,17,28,41] . Late HAT shows a lower incidence, ranging from 1% to 25% [38,42] .…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies show contradictory results [1,9,17,28,41] but, a metaanalysis on HAT found no significant difference with an incidence of 3.1% and 4.6% in LDLT and DDLT, respectively [28] . Furthermore, it was reported that arterial anastomosis with operation microscope or loupe mangnification did not show any difference in incidence HAT [9,17,28,41] . Late HAT shows a lower incidence, ranging from 1% to 25% [38,42] .…”
Section: Incidencementioning
confidence: 99%
“…They reported that there were no differences in incidence among transplantation centers worldwide [2,28] . Median times to the occurrence detection of early and late HAT were respectively 6.9 postoperative days (range: 1-17.5) and 6 mo (range: 1.8-79 mo) [17] . In literature, it does not confirm that HAT incidence in LDLT is significantly lower or higher compared to HAT incidence in DDLT.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…Early HAT is generally related to technical problems and can have serious consequences [115] . Emergent interventions are usually needed with early HAT because of its related ischemia/necrosis of the bile duct system [114] . Although urgent re-transplantation is considered the main treatment for early HAT, endovascular interventions including percutaneous transluminal angioplasty (PTA), intra-arterial thrombolysis (IAT) in selective cases, and stent placement may be alternative treatments [117,118] .…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…HAT represents more than 50% of all arterial complications following LT and it is divided into early (< 4 wk from LT) and late HAT (> 4 wk from LT) [114][115][116] . Early HAT is generally related to technical problems and can have serious consequences [115] .…”
Section: Vascular Complicationsmentioning
confidence: 99%